Improving construction industry process interoperability with Industry Foundation Processes (IFP). (October 2018) - Golzarpoor, Behrooz; Haas, Carl T.; Rayside, Derek; Kang, Seokyoung; Weston, Matthew
Abstract: With massive amounts of information generated during the life cycle of large-scale construction projects, interoperability among project stakeholders' information systems is a requirement for effective and timely communication, collaboration, and information exchange, and ultimately for project success. While data interoperability has been substantially improved by initiatives such as IFC (Industry Foundation Classes) standardizing construction industry data, emphasis on process interoperability which facilitates timely and effective exchange of information via interaction of workflow processes is in its early stage. By conforming to a reference model such as IFP (Industry Foundation Processes), project stakeholders can communicate and collaborate using workflow processes while abstracting the information exchange to essential items to preserve their privacy. This paper explores interoperability in the AEC/FM domain, reviews the main components of the IFP system, presents two IFP interoperability models, and discusses their relationships with the IFP system. The models are demonstrated with specific examples and implemented with a process customization framework based on workflow inheritance rules. Interoperability models that conform to the IFP system not only allow seamless information exchange but can also yield active interaction and communication among stakeholders.